ANALYSIS OF THE FINANCIAL PERFORMANCE OF PT. MAYORA INDAH TBK BASED ON PROFITABILITY AND LIQUIDITY RATIO: A COMPREHENSIVE STUDY - Nababan, Cintia; Sinurat, Mangasa; Munte, Mei Hotma Mariati (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This research has high urgency in the context of the dynamics of Indonesia's food and beverage manufacturing industry post-pandemic, where global economic fluctuations and changes in consumption patterns demand a thorough evaluation of the company's financial performance. As a market leader with a strategic product portfolio, the performance analysis of PT. Mayora Indah Tbk is crucial to map business resilience in an era of economic volatility. The study makes a dual contribution: theoretically by enriching the literature on the application of financial ratios in the consumer goods industry, and practically by presenting actual data-driven strategic recommendations for company management. The quantitative descriptive research method was applied to the 2021-2023 financial statement data, with the analysis focusing on profitability (ROE and NPM) and liquidity (CR and QR) ratios. The findings revealed that the company managed to maintain very strong liquidity above industry standards, while profitability showed an upward trend although there was still room for optimization. This research is an important benchmark for the industry in evaluating working capital management strategies and increasing profitability amid economic uncertainty.